Pengaruh Kualitas Pelayanan Perpajakan, Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak - Devita Devita; Dara Nabila; Lamsina Harahap; Dini Vientiany (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of this research is to determine the influence of tax service quality and tax sanctions on taxpayer compliance. This research also aims to find out whether the quality of tax services and tax sanctions have a significant relationship with taxpayer compliance. This research uses a quantitative approach with a focus on explanatory research, which aims to reveal the cause-and-effect relationship between independent variables, namely the quality of tax services and tax sanctions, on the dependent variable, namely taxpayer compliance in Medan City, Indonesia. This research shows that the quality of tax services and tax sanctions are important factors that influence taxpayer compliance. Therefore, the DGT needs to improve the quality of tax services and implement effective tax sanctions to increase taxpayer compliance.